PERSEPSI MAHASISWA PPLK PROGRAM STUDI PENDIDIKAN BAHASA INGGRIS FBS UNP TERHADAP TUGAS DAN TANGGUNG JAWAB GURU PAMONG - Fatimah, Sitti (English Department FBS UNP, 2010)
This article is written based on the research aiming at describing the duties and responsibilities of supervising teachers during the conduction of student-teaching program in the period of January-June 2010 by English department students. The data was taken from the questionnaires given to the student-teachers whose perceptions about the supervising teachersâ€™ duties and responsibilities. Generally, the questionnaires asked the sample about the performing of duties and responsibilities by supervising teachers in three periods: observation, guided teaching and independent teaching period. Based on the data Â it is found that although in the third (independent teaching) period the supervising teachers performed their duties and responsibilities well, both in the first (observation) and second (guided teaching) period the supervising teachers did not perform their duties and responsibilities as they should have been.